2005
DOI: 10.1007/s11172-005-0337-x
|View full text |Cite
|
Sign up to set email alerts
|

Nature of weak inter- and intramolecular interactions in crystals. 5. Interactions Na...H—B in a crystal of sodium salt of charge-compensated nido-carborane [9-SMe2-7,8-C2B9H10]−

Abstract: The character of electron density distribution in the C 2 B 3 open face, the influence of the SMe 2 group on the character of electron density distribution, and the nature of the so dium-anion interaction were studied based on the data of high resolution X ray diffraction study of crystals of the sodium salt of charge compensated nido carborane [9 SMe 2 7,8 C 2 B 9 H 10 ] -and quantum chemical calculations for the Na...H-B bonded dimer, the isolated [9 SMe 2 7,8 C 2 B 9 H 10 ] -anion, and the [7,8 C 2 B 9 H 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The topology of EDD for nido-5,6-C 2 B 8 H 12 has something in common with that reported for closo-and nido-clusters earlier [8][9][10][11][12][13][14][15][16]. Firstly, the bonding in the cage is realized both via multicenter and two-center bonds of reduced order.…”
Section: Neutral Nido-56-c 2 B 8 H 12supporting
confidence: 77%
See 1 more Smart Citation
“…The topology of EDD for nido-5,6-C 2 B 8 H 12 has something in common with that reported for closo-and nido-clusters earlier [8][9][10][11][12][13][14][15][16]. Firstly, the bonding in the cage is realized both via multicenter and two-center bonds of reduced order.…”
Section: Neutral Nido-56-c 2 B 8 H 12supporting
confidence: 77%
“…The works using AIM were reported only for a limited number of boranes and carboranes and concerned mainly closo species [8][9][10][11][12][13][14][15]. For these types of clusters it was shown that stabilization of electron-deficient systems is achieved both by accumulation of electronic charge along the bond paths and by its delocalization over the polyhedron surface.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Another approach includes alkylation of the 9-methylthio derivative of nido-carborane [9-MeS-7,8-C 2 B 9 H 11 ] -to give the corresponding 9-alkylmethylsulfonium derivatives 9-R(CH 2 ) n (Me)S-7,8-C 2 B 9 H 11 . [18][19][20] In contrast to the B-dialkylsulfonium derivatives of other polyhedral boron hydrides where racemization at the sulfur atom already proceeds very fast at ambient temperature, [21] in the case of nido-carborane derivatives 9-R(CH 2 ) n (Me)S-7,8-C 2 B 9 H 11 , the activation barrier is much higher because of an interaction of the sulfur lone pair electrons with the B(9)-B(10) antibonding orbital electrons of the nido-carborane cage [22] , and no racemization is observed up to 333 K. [20] As a result, the asymmetrically substituted nido-carborane derivatives 9-R(CH 2 ) n (Me)S-7,8-C 2 B 9 H 11 exist as mixtures of diastereomers which are not very suitable for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Experimental data relating to electron density (ED) distribution are limited, to the best of our knowledge, to a metallacarborane of nontransition metals: {Na(thf) 2 [9-SMe 2 -7,8-C 2 B 9 H 10 ]} 2 . [26] QTAIM [27] is a powerful method with which to study various types of chemical bonding. In this method, topological analysis of the three-dimensional ED is carried out to divide space into atomic basins with surfaces of zero electronic flux.…”
Section: Introductionmentioning
confidence: 99%